Yard's junk shed. - Barrett, Terra (2014)
Yard's junk shed by the water which is filled with fishing gear such as nets, traps, rope, bouys, floaters, a caplin dipper, a squid roller, fish tubs, diesel fuel for Yard's boat and containers to hold lobsters. The rear half of the shed was built by Yard's father Henry Yard in the 1930s; the front half was built by Yard in the mid 2000s.